Association of single nucleotide polymorphisms in the CFH, ARMS2 and HTRA1 genes with risk of developing age related macular degeneration in Egyptian patients - Abbas, Radwa Ossama (AUC Knowledge Fountain, 2013)
Age related macular degeneration (AMD) is one of the leading causes of blindness in the elderly worldwide. Due to earlier clinical observations that AMD concentrates in families, a genetic component to the disease has been suggested. Several genetic studies have identified areas of association with AMD on chromosomes 1q31 and 10q26. On chromosome 1q31 the most famous single nucleotide polymorphism (SNP) to be linked to AMD was rs1061170 on the complement factor H gene (CFH). This SNP was studied in several populations and was found to be highly associated with AMD in most Caucasian populations with odds Ratio (OR) reaching 9.79 for CC homozygous and 4.36 for CT heterozygous in some cases. However in Japan, China, Korea and South Africa no or weak association was found. Other SNPs on chromosome 10q26 were also associated with AMD. SNP rs10490924 (Ala69Ser) on the age related maculopathy susceptibility 2 gene (ARMS2) was associated with AMD in the USA, Germany, China, Turkey and India with OR values reaching 8.61 for homozygotes. On the HTRA1 (HtrA serine peptidase 1) gene rs11200638 was associated with AMD in China, India and the USA with OR reaching up to 7.9 for individuals homozygous for the risk allele. Due to varying results of association in different populations we aimed to examine the association between AMD and SNPs on CFH, ARMS2 and HTRA1 in Egyptian patients, a previously unstudied population. We recruited 26 individuals diagnosed with AMD and twenty unrelated age matched controls. Genotyping was carried out through polymerase chain reaction (PCR) followed by allele-specific restriction digestion and direct sequencing for some cases. We found all three SNPs to be significantly associated with AMD. For rs1061170 the OR for heterozygous TC genotype was 5.5 (95% CI: 1.145-26.412). While for the combined TC+CC genotypes the OR was 8 (95% CI: 1.726-37.090). Similarly, for rs10490924 the OR for heterozygous TG genotype was 4.667 (95% CI: 1.187-18.352) and for the combined TG+TT genotypes it was 7 (95% CI: 1.852-26.461). In HTRA1 rs11200638 OR for GA genotype was 5 (95% CI: 1.195-20.922) and for combined GA+AA genotypes it was 6 (95% CI: 1.456-24.733). We conclude that our study results indicate a trend of association between the three polymorphisms studied and AMD in agreement with findings in Caucasian populations.